2008
DOI: 10.3200/jach.57.3.281-290
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, Tobacco, Illicit Drugs, and Performance Enhancers: A Comparison of Use by College Student Athletes and Nonathletes

Abstract: Objective-The authors compared the prevalence and pattern of substance use in undergraduate student athletes and nonathletes from 2005-2006. Participants-Authors collected data from male (n = 418) and female (n = 475) student athletes and nonathletes from [2005][2006]. Methods-The authors administered self-report questionnaires to assess prevalence, quantity, and frequency of alcohol and drug use, and to determine patterns of student athletes' alcohol and drug use during their athletic season versus out of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
116
4
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(133 citation statements)
references
References 24 publications
10
116
4
3
Order By: Relevance
“…Such findings are applicable to both male and female college athletes (Yusko et al, 2008). White male college athletes are the most likely to engage in binge drinking (Yusko et al, 2008).…”
Section: Alcohol Usementioning
confidence: 92%
See 4 more Smart Citations
“…Such findings are applicable to both male and female college athletes (Yusko et al, 2008). White male college athletes are the most likely to engage in binge drinking (Yusko et al, 2008).…”
Section: Alcohol Usementioning
confidence: 92%
“…In addition to higher rates of alcohol consumption, college athletes are significantly more likely than non-athletes to use certain forms of illicit drugs and performance enhancing drugs (PEDs, substances used by people to improve their performance in the sports in which they participate) (Yusko et al, 2008). Yusko and colleagues (2008) found that male college athletes are more likely than nonathletes to use methamphetamines, banned performance enhancers, and approved performance enhancers.…”
Section: Alcohol Usementioning
confidence: 99%
See 3 more Smart Citations